02.13 Il-17f contributes to human chronic inflammation in synovial tissue: Preclinical evidence with dual il-17a and il-17f inhibition with bimekizumab in psoriatic arthritis. (1st March 2017) - Maroof, Ash; Baeten, Dominique; Archer, Sophie; Griffiths, Meryn; Shaw, Stevan
Abstract : Background: IL-17A is an established target in several chronic immune-mediated inflammatory diseases; IL-17F, sharing significant structural homology and overlapping biological function with IL-17A, 1 is a relatively understudied cytokine. Bimekizumab is a humanised monoclonal IgG1 antibody that potently and selectively neutralises the biological function of both IL-17A and IL-17F. Using preclinical human in vitro models we studied the contribution of IL-17F to inflammation, via stimulation and blocking assays, in joint cells from patients with psoriatic arthritis (PsA). Materials and methods: Immunostaining was performed on synovial tissue from patients with PsA to probe for IL-17F. Recombinant IL-17A and IL-17F, with/without TNFα, were added to synoviocytes from patients with PsA, to examine their effect on inflammatory cytokine production. A complex in vitro assay was developed, using pro-inflammatory mediators from sorted Th17 cells, to explore the mechanism of action of bimekizumab and relative contributions of IL-17A and IL-17F to chronic disease. The Th17-cell supernatant profile had a complex mix of disease-relevant pro-inflammatory cytokines akin to those found elevated in joint tissue biopsies from patients with PsA. IL-17-isoform-specific blocking antibodies provided an overview of the individual and collective influence of IL-17A and IL-17F in regulating key disease-pathology-relevant cytokine and chemokine production. Results: IL-17F protein was detected in inflamed synovium from patients with PsA. Stimulation of normal synoviocytes with recombinant IL-17A or IL-17F promoted qualitatively similar responses, notably induction of key pro-inflammatory mediators (eg, IL-8 and IL-6), albeit to a lesser extent with IL-17F than IL-17A. Similar results were obtained in synoviocytes from patients with PsA, stimulated in the presence of TNFα. When synoviocytes from patients with PsA were stimulated with Th17-cell supernatant, dual IL-17A and IL-17F inhibition with bimekizumab resulted in a greater downregulation of IL-6 (42% lower; p<0.05) and IL-8 (35.4% lower; p<0.05) expression than inhibition of IL-17A alone. Similar results were obtained using monospecific anti-IL-17A and anti-IL-17F antibodies. Conclusions: Data support hypotheses that IL-17F contributes to human tissue inflammation in joints, beyond IL-17A alone, and that dual inhibition of IL-17A and IL-17F may be therapeutically beneficial in immune-mediated inflammatory diseases. Acknowledgements: The authors thank the subjects and their caregivers in addition to the investigators and their teams who contributed to this study. This study was funded by UCB Pharma. The authors acknowledge the contributions of Tim Smallie, of UCB, Louise Healy, formerly of UCB, for their work on functional characterisation of bimekizumab. The authors also acknowledge the contribution of Catherine Simpson, of UCB, for flow cytometry cell sorting support, Remi Okoye, of UCB, for the immunohistochemistry work, and Iris Blijdorp of the Academic Medical Centre, Amsterdam, for work on blockade experiments in synoviocytes. The authors would like to acknowledge Ailsa Dermody, PhD, of iMed Comms, an Ashfield Company, part of UDG Healthcare plc, for editorial assistance that was funded by UCB Pharma. Reference: Johansen C, Usher PA, Kjellerup RB, et al, . . Characterisation of the interleukin-17 isoforms and receptors in lesional psoriatic skin. Br J Dermatol 2009; 160(2): 319-24.